Isolation and Comparative Characterization of Saccharomyces cerevisiae from Indigenous Fermented Tea “Miang” under Fermentation Stress Conditions - PHOVISAY, Somsay; Phimsala, Phuangsavat; PHASOUK, Amphone; Nortualee, Leulee; Chanthakhoun, Vongpasith (International Journal on Food, Agriculture and Natural Resources, 2025)
This study investigated the isolation and comparative characterization of Saccharomyces cerevisiae strains from indigenous fermented tea “Miang” and their comparison with the commercial strain Saccharomyces cerevisiae EC1118 under various fermentation stress conditions. Yeast strains were isolated from Miang, and their performance was evaluated in terms of sugar utilization, pH tolerance, ethanol concentration, potassium metabisulfite (KMS), sodium chloride (NaCl), and osmotic pressure tolerance. Optical density (OD) at 600 nm was measured using a spectrophotometer over a 24-h incubation period to assess yeast growth. The results showed that the newly isolated strain, S. cerevisiae MXH-1, exhibited superior growth in ethanol concentrations of up to 15%, with an OD increase of 1.22 compared to 0.12 for EC1118. Additionally, MXH-1 demonstrated enhanced tolerance to KMS at 200 ppm and NaCl at 5%, with significantly higher OD changes than EC1118. These findings underscore the potential of S. cerevisiae MXH-1 for industrial applications, particularly in high-stress fermentation processes. This study provides valuable insights into the fermentation capabilities of indigenous yeast strains under challenging environmental conditions positioning MXH-1 as a promising candidate for food and beverage industries. Further research is recommended to explore the genetic mechanisms underlying its resilience and tolerance to fermentation stressors.